Anaerobic performance after endurance strength training in hypobaric environment - Álvarez-Herms, J.; Julià-Sánchez, S.; Corbi, F.; Pagès, T.; Viscor, G. (Science & Sports, 2014)
Objective: This study was aimed to assess anaerobic capacity after an endurance strength training (EST) protocol for 4 weeks. Methods: A group of volunteers (n = 5) trained in a hypobaric chamber at a simulated altitude of 2500 m (HYP), while the other (n = 7), trained at sea level (NOR). Anaerobic power was tested before and after the training protocol through the widely used Bosco's vertical jump test procedures: squat jump (SJ), countermovement jump (CMJ) and sixty seconds repeated maximal countermovement vertical jump (60CMJ). The mean height for the whole 60CMJ test (cm), partial heights every 5 and 15 sec were measured and the fatigue index (60CMJ/CMJ] was calculated. Results: Hypoxic training significantly improved mean height for 60CMJ by 6.75% (P = 0.029) in comparison to normoxic training. The fatigue index was also significantly lower (P = 0.031) in the HYP group than in the NOR group. Partial heights at 45-60" intervals increased by 32.9% in the post-training test for the HYP group (P = 0.004), compared to a lower improvement of 21.9% for the NOR group (P = 0.022). Conclusions: Our study shows a better anaerobic capacity after EST training at a moderate simulated altitude compared with that attained following the same training protocol at sea level.